2022
DOI: 10.1002/adem.202101520
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Module of SiGe Bulk Alloys Forming p‐n Junction at the Hot Side

Abstract: Thermoelectric power generation is a potential technology for providing green energy. It is expected to be able to convert enormous amounts of waste heat to electrical energy. To realize this technology, further increases in conversion efficiency and durability are essential. In particular, durability is a critical issue, especially for harnessing high‐temperature heat sources. Thus, a thermoelectric module of SiGe is fabricated without electrodes at the hot side, which is the main cause of aging. Electronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…There are two possible reasons for the decrease in R in near room temperature, i.e., the ρ of TEcM exhibits a tendency to decrease and then increase (Figure S8, Supporting Information), and the ρ c is likely to decrease as the temperature rises. [ 55 ] Additionally, the measured thermal conductivity (κ) of the TE device was slightly higher than the theoretical value. This is due to the fact that the theoretical κ is the κ of TEcM, while the measured κ includes the contribution of the Cu electrodes, TEiM, and AlN substrates.…”
Section: Resultsmentioning
confidence: 93%
“…There are two possible reasons for the decrease in R in near room temperature, i.e., the ρ of TEcM exhibits a tendency to decrease and then increase (Figure S8, Supporting Information), and the ρ c is likely to decrease as the temperature rises. [ 55 ] Additionally, the measured thermal conductivity (κ) of the TE device was slightly higher than the theoretical value. This is due to the fact that the theoretical κ is the κ of TEcM, while the measured κ includes the contribution of the Cu electrodes, TEiM, and AlN substrates.…”
Section: Resultsmentioning
confidence: 93%
“…Although, this concept of device is scarce, few instances are present where the array of pn-junctions were used. [78,[150][151][152][153][154] Fabrication of directly bonded p-and n-type materials were realized using polycrystalline FeSi 2 which facilitates the operation of the devices at high temperature and in oxidizing environment. [155] These devices possess U-shaped geometry (Figure 15B) and FeSi 2 at elevated temperature makes a metallic bonding between the n-and p-type materials.…”
Section: Bulk Tegs Employing Pn-junction At the Hot Sidementioning
confidence: 99%
“…Although, this concept of device is scarce, few instances are present where the array of pn‐junctions were used [78,150–154] . Fabrication of directly bonded p‐ and n‐type materials were realized using polycrystalline FeSi 2 which facilitates the operation of the devices at high temperature and in oxidizing environment [155] .…”
Section: Structural Design Of Thermoelectric Devicesmentioning
confidence: 99%
“…Silicongermanium alloys are the most common, with multiple studies studying the addition of germanium to silicon nanowires, [131] silicon thin films [40] and bulk silicon. [132] The primary reason for reduced thermal conductivity is due to increased alloy scattering that suppresses high-frequency phonons. [133] For example, Song et al [134] found a 40% decrease in lattice thermal conductivity in a SiGe alloy.…”
Section: Siliconmentioning
confidence: 99%